PENGEMBANGAN MEDIA GENIALLY UNTUK MENINGKATKAN KETERAMPILAN MEMBACA (MAHARAH QIRĀ’AH) MAHASISWA DI PERGURUAN TINGGI - Sintya Rahmadewi; Nida Husnia Ramadhani; Miftahul Huda (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to develop interactive learning media based on the Genially application to improve reading skills (maharah qirā’ah) among second-semester university students. The background of this research is based on the low intrinsic motivation of students to read Arabic texts, high levels of linguistic anxiety, and a learning approach that still emphasizes memorization and grammar structure, without providing sufficient space for contextual understanding. The research method used is Research and Development (R&D) with the 4D model (Define, Design, Develop, Disseminate), although this study only reached the development stage. The media was validated by two content experts and two media experts. The validation results showed that the media received an average score of 86.3% from content experts and 98% from media experts, both of which fall under the